Ethnopharmocological study of medicinal plants used for treatment of skin diseases by herbalists in Northwestern region of Algeria - Razika Hantour; Yasmina Benabdesslem; Mustapha Diaf; Kadda Hachem; Samia Ghomari (PLoS ONE, 2026)
Background Skin disease is a major public health concern worldwide, particularly in developing countries. Despite the rich diversity of medicinal plants and strong traditional healing practices in Algeria, the dependence on imported pharmaceuticals remains high. This study documents and analyzes traditional herbal knowledge related to the treatment of skin diseases in Northwestern Algeria (Mascara, Saïda, and Sidi Bel Abbès) with the aim to preserve and scientifically validate this ethnomedicinal heritage. Methods A total of 117 herbalists (110 men and seven women) were interviewed using semi-structured questionnaires between September 2023 and July 2024. Data were analyzed using quantitative ethnobotanical indices, including the Relative Frequency of Citations (RFC) and Plant Part Value (PPV), to assess the cultural significance and usage frequency of medicinal species. Results A total of 73 plant species belonging to 29 families have been reported for the treatment of various skin ailments. The most abundant families were Lamiaceae , Asteraceae , Cucurbitaceae , Liliaceae , Cupressaceae , and Fabaceae . Allium sativum L. and Thymus vulgaris L. showed the highest RFC values (0.175 and 0.124, respectively). Leaves were the most frequently used plant parts (PPV = 0.48; 47.6%), followed by fruits (PPV = 0.12; 11.6%), and seeds (PPV = 0.09; 8.9%). Most of the remedies were prepared from dried plants (65.31%), powders (39.9%), and decoctions (22.55%) being the main preparation methods. Topical application (35.2%), poultices (30%), and rinsing (25%) were the most common modes of administration. The most frequently treated skin conditions were eczema, psoriasis, and acne. Conclusions This study highlights the remarkable ethnopharmacological knowledge preserved among herbalists in Northwestern Algeria, including women’s traditional roles in medicinal practices. The documentation of these findings not only assists preserve valuable cultural heritage but also provides a foundation for future pharmacological research and the sustainable use of the rich medicinal flora of Algeria.